Development of Physical Science Teaching Module Phase F for Physically Impaired Students in Special Schools on the Nature of Light - Sujono, Adelia Putri; Umar, Masri Kudrat; Odja, Abdul Haris (Kasuari: Physics Education Journal (KPEJ), 2024)
This research aims to produce a pahse F science teaching module for disabled students that is feasible, practical, and effective. This research was carried out at the Bone Bolango state special school. This type of research is research and development using the ADDIE development model and was tested in class XII of Bonebolango State Special School. The results of this research show that: 1) the teaching module developed is very valid and suitable for use in learning, 2) the teaching module developed is practically determined by the average percentage of learning implementation during three meetings which reached 88,36% with very good criteria, 3) effective teaching modules developed are determined through the average percentage of student activity during three meetings which reached 79,16% with very good criteria, and the completeness of student learning outcomes is determined through the average percentage of cognitive assessments during three meetings which reached 88,89% with very good criteria, the average percentage of attitude assessments during three meetings which reached 79,16% with very good criteria, and the average percentage of skills assessments during three meetings which reached 82,77% with very good criteria good based on this, it can be concluded that the physics teaching module on the nature of light material developed is feasible, practical and effective.